Comparison between Baud Rates for Serial Video Data Transmission over Zigbee in Wireless Sensor Network - Khedkar, Mrunal; Asutkar, G.M (International Journal of Computer Sciences and Engineering, 2019)
For transmitting real time information (over the standalone network), video wireless sensor networks are becoming more popular. As the video data is inherently very large in size, it requires more memory, greater processing speed and larger bandwidth for its transmission. In this paper, zigbee is used for video transmission, as it economical and consumes less power. The video is initially compressed using discrete cosine transform (DCT) based compression technique and then transmitted over zigbee using two different baud rates. The same video is transmitted number of times at two different baud rates, which helps in comparing and getting more accurate values of various parameters for video transmission at two different baud rates. Comparison is carried out by calculating average values of image parameters, transmission time, reception time, frame loss and frame delay independently. Finally reliable and efficient baud rate is found out for video data transmission over zigbee network.